Art, archives and shifting objectivities : the plurality of knowledges and the work of David Wojnarowicz and Minna Henriksson - Lassinaro, Kaisa (2020)
This thesis looks at the production of knowledge and the myth of objectivity. Its starting points are the practices and thinking around archival knowledge. What kinds of knowledges can emerge through artistic practice? How is the archive activated to its subversive potential so other histories may emerge? By considering the places and materiality of the archive and art, this enquiry looks at their means in bringing about hidden and subjugated knowledges.